The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1055/s-2004-815788
|View full text |Cite
|
Sign up to set email alerts
|

Neuroradiological Findings (MRS, MRI, SPECT) in Infantile Neuronal Ceroid-Lipofuscinosis (Infantile CLN1) at Different Stages of the Disease

Abstract: Infantile neuronal ceroid-lipofuscinosis (infantile CLN1) is a progressive and uniformly fatal lysosomal storage disease of the nervous system. The purpose of this study was to compare the findings of various radiological examinations of the brain in the course of infantile CLN1 in order to evaluate the relative usefulness of the methods and their potential for monitoring therapeutic interventions. We examined eight infantile CLN1 patients, 51 studies, in various stages of the disease--preclinical to late stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 22 publications
(25 reference statements)
2
35
1
Order By: Relevance
“…Regarding brain MRI, our patients showed similar findings to what has previously been reported by other authors (Santavuori et al, 1992(Santavuori et al, , 2000Vanhanen et al, 1995Vanhanen et al, , 2004.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding brain MRI, our patients showed similar findings to what has previously been reported by other authors (Santavuori et al, 1992(Santavuori et al, , 2000Vanhanen et al, 1995Vanhanen et al, , 2004.…”
Section: Discussionsupporting
confidence: 92%
“…Extrapolation of our previously published measurements of NAA in the thalamus 11 suggest that NAA in the thalamus may be in the normal range for a few months after birth; previous measurements 22 on very young children with INCL demonstrated normal NAA in the thalamus of a 2 month old child and a slight deficit of NAA in the thalamus of a 4 month old child. Thus, the relative order of volume loss (cerebrum before thalamus) that we report in this study is concordant with the order of previously reported MRS changes in humans.…”
Section: Discussionsupporting
confidence: 56%
“…Extrapolation of the cerebellum-to-cerebrum volume ratio suggests that the cerebral volume may never have been normal, not even in the fetus. A previous MRS study 22 found low NAA in the cerebral white matter of a patient at the age of 4 months; in the separately-reported MRS component of the current study 11 , we found that extrapolation of cerebral NAA levels beyond the age of our youngest patient does not appear to intersect the normal curve. NAA is produced mainly (or perhaps exclusively) by healthy neurons 23, 24 , and a decline in the level of NAA indicates loss or injury of neurons; logically, loss or injury of neurons should precede atrophy, and therefore the timing of our cerebral atrophy observations is consistent with the timing of NAA decline observed in the previous MRS reports.…”
Section: Discussioncontrasting
confidence: 54%
“…Conventional MR imaging and CT have been used to demonstrate the presence of cerebral atrophy in multiple forms of neuronal ceroid lipofuscinosis. [13][14][15][16] However, atrophic grading using conventional MR imaging is only a subjective measure of disease severity. A diffuse hyperintensity of cerebral white matter has been reported in LINCL patients.…”
Section: Discussionmentioning
confidence: 99%